Real-World Life Analysis of a Continuous Glucose Monitoring and Smart Insulin Pen System in Type 1 Diabetes: A Cohort Study - Paola Pantanetti; Giovanni Cangelosi; Sara Morales Palomares; Gaetano Ferrara; Federico Biondini; Stefano Mancin; Gabriele Caggianelli; Mauro Parozzi; Marco Sguanci; Fabio Petrelli (Diabetology)
Background: Diabetes affects over 460 million people worldwide and represents a growing public health challenge driven largely by dietary and lifestyle factors. While Type 2 diabetes (T2D) is more prevalent, Type 1 diabetes (T1D) presents unique therapeutic challenges, particularly in younger individuals. Advances in diabetes management, such as continuous glucose monitoring (CGM), insulin pumps (IP), and, more recently, smart multiple dose injection (MDI) pens, have significantly enhanced glycemic control and improved patients’ quality of life. Aim: This study aims to evaluate the baseline characteristics of patients switching from MDI therapy to the Medtronic Smart MDI system [composed of a smart insulin pen (InPenTM) and a connected CGM Medtronic SimpleraTM sensor] and to assess its impact on glycemic outcomes over different time periods (14, 30, and 90 days). Methods: A retrospective observational study was conducted among adults with T1D who initiated Medtronic Smart MDI therapy. Participants were enrolled voluntarily at the Diabetes and Nutrition Clinic in Ast Fermo, Marche Region, Italy. Glycemic parameters were monitored using CGM data and analyzed with descriptive statistics, including mean, standard deviation (SD), and interquartile range (IQR). Comparisons across time periods were performed using the Wilcoxon signed-rank test, with statistical significance set at p < 0.05. Results: This study included 21 participants with a mean age of 51.5 years, a mean BMI of 24.7, and a mean duration of T1D of 21.9 years. The transition from a traditional MDI system to the Smart MDI system resulted in significant improvements in key glycemic parameters: mean Sensor Glucose (SG) decreased from 171.0 mg/dL to 153.5 mg/dL (p = 0.035), Time In Range (TIR) increased from 58.0% to 64.4% (p = 0.005), and time above range (TAR; >180 mg/dL) decreased from 39.0% to 34.2% (p = 0.015). No significant differences were observed in the time below range (TBR). Conclusions: The transition to the Medtronic Smart MDI system significantly enhanced glycemic control by lowering mean glucose levels and increasing TIR. These findings highlight its efficacy in improving hyperglycemia management while maintaining a stable risk of hypoglycemia.